La traduction, instrument de légitimité littéraire
Translation plays a crucial role in increasing the legitimacy of national literatures. In this paper I underline the role played by the French State in sustaining translation, through programs such as that of CNL, namely in Portugal. Such governmental measures have important consequences on the promotion of quality literature which, because it is not very commercial, tends to be less known abroad.